2007
DOI: 10.1016/j.yexcr.2006.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Erk1/2 MAPK and caldesmon differentially regulate podosome dynamics in A7r5 vascular smooth muscle cells

Abstract: We tested the hypothesis that the MEK/Erk/caldesmon phosphorylation cascade regulates PKCmediated podosome dynamics in A7r5 cells. We observed the phosphorylation of MEK, Erk and caldesmon, and their translocation to the podosomes upon phorbol dibutyrate (PDBu) stimulation, together with the nuclear translocation of phospho-MEK and phospho-Erk. After MEK inhibition by U0126, Erk translocated to the interconnected actin-rich columns but failed to translocate to the nucleus, suggesting that podosomes served as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 50 publications
2
60
0
1
Order By: Relevance
“…Such an effect should be readily testable by biochemical experiments. Another notable finding in these studies is that ERK-phosphorylated CaD (although not so clear about PAK-phosphorylated CaD) is localized at the ring of podosomes 186 where Tm5a/5b was found in the osteoclasts. 58 Whether such colocalization suggests interactions or common targets is worthy of further investigation.…”
Section: Phosphorylation As a Regulatory Mechanismmentioning
confidence: 92%
See 2 more Smart Citations
“…Such an effect should be readily testable by biochemical experiments. Another notable finding in these studies is that ERK-phosphorylated CaD (although not so clear about PAK-phosphorylated CaD) is localized at the ring of podosomes 186 where Tm5a/5b was found in the osteoclasts. 58 Whether such colocalization suggests interactions or common targets is worthy of further investigation.…”
Section: Phosphorylation As a Regulatory Mechanismmentioning
confidence: 92%
“…Interestingly, l-CaD is present in such podosomes 185 and is phosphorylated at ERK sites. 186 By overexpressing a phosphorylation-deficient CaD-GFP mutant it was found that, although both the size and the lifetime of the podosomes are modulated by ERK-mediated CaD phosphorylation, the modes of ERK and CaD in their modulation of the formation and dynamics of podosomes are different. 186 This suggests involvement of other players in addition to ERK.…”
Section: Phosphorylation As a Regulatory Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which phorbol ester activates MEK/ ERK and causes vascular contraction has been established. [121] On the other hand, previous studies that inspected the mechanisms underlying arterial contractions induced by fluoride or thromboxane A2 have reported variable findings with regard to the contraction triggered by…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…There is a subset of proteins that are thought to have a role in regulating podosome half-life, and that may be important regulators of podosome structure and function. Recently it has been shown that inhibition of Erk1/2 phosphorylation leads to increased podosome lifetime in PDBu-stimulated A7R5 cells (Gu et al, 2007). Through detailed mathematical modeling, it has been shown that increased podosome lifetime was mainly affected by the decreased rate constant for podosome disassembly, which indicated that Erk1/2 phosphorylation is involved in facilitating podosome disassembly.…”
Section: Journal Of Cell Science 121 (14)mentioning
confidence: 99%